THE RESPONSE OF BLACK RICE TOWARDS ALUMINIUM TOXICITY IN GERMINATION PHASE - Mahmuda, Arrum; ., Asnawati; Ruliyansyah, Agus (Jurnal Sains Mahasiswa Pertanian, 2020)
Black rice is a type of rice which has high anthocyanins content functioning as antioxidants which are beneficial for health. Superior seed can be used to improve the production of black rice. However, local seeds with Aluminium tolerance are not available. This research aims to find out the response of several varieties of black rice towards Al toxicity in germination phase. This research used several black rise varieties namely Senakin, Tabah, Gula and Melawi variety. Meanwhile, inpara 2 variety was used as a comperative seed with Al tolerance and Cibogo variety was used as a comperative seed which is susceptible to Al. Seed selections is conducted to obtain seeds that has the potential to grow subobtimal condition. seeds were placed on straw paper which has been sprayed with 150 ppm Al solution and rolled. Comparison (I) Senakin, Tabah, Gula and Melawi variety were significantly different from Inpara 2 and Cibogo variety in observation variable Germination Percentage (GP), Vigor Index (VI), Grow Rate (GR) and Radicle Length (RL). Comparison (II) Senakin variety was significantly different from Tabah, Gula and Melawi variety in observation variable GP, VI, GR and RL. Comparison (III) Tabah variety was significantly different from Gula and Melawi variety in observation variable GP, VI, GR and RL. Comparison (IV) Gula variety was significantly different from Melawi variety in observation variable GP, VI, and GR, yet not significantly different in variable RL. Comparison (V) Inpara 2 variety was significantly different from Cibogo variety in observation variable GP and VI yet not significantly different in variable GR and RL.Keywords: Aluminium Toxicity, Black Rice, Germination, Susceptible, Tolerance, Variety